The use of audiovisual resources in the training of history teachers (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2025)
This paper addresses considerations, perspectives, and teaching approaches to the use of audiovisual materials (documentaries, fiction, and docu-fiction) in history classes at non-university higher education levels. To this end, a survey was implemented as an instrument in 2024 and 2025, among teachers from two teacher training institutes in the province of Buenos Aires who teach history courses at the tertiary level. The analysis examines the responses obtained in relation to the current context of teacher training within the framework of the implementation of new study programs, the update of the new academic framework, the current status of curriculum development materials produced for teaching based on the official proposal, the contributions of some classic studies on film and more recent productions on audiovisual materials and history teaching. In this way, we place the responses provided in the survey through the prism of this latest research.
Keywords: history; audiovisuals; teacher training